2012
DOI: 10.3126/jpn.v2i4.6883
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological analysis of testicular tumors

Abstract: Background: Testicular cancers are rare in most countries. However, in many western countries its incidence has been increasing since the middle of the twentieth century. A definite geographic and racial distribution is seen in testicular tumors. The purpose of the study was to analyze the pattern and distribution of testicular cancers in one of the hospital in Nepal. Materials and methods:This was a retrospective study, in which cases were retrieved from the computer database between September 2006 and August… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…Teratocarcinoma encountered 12.1% incidence in this study, which is comparable to the studies done by Naqvi et al [13] and Karki and Bhatta. [19] Yolk sac tumor accounted for 5.22% of this study, which was comparable to the figures 5.8% and 6.8% given by Deore et al [18] and Naqvi et al [13] Most of the cases were seen in first decade. The incidence of other mixed germ cell tumors, that is, embryonal carcinoma and seminoma and Teratoma and seminoma was 4.3% and 3.4%, respectively which is comparable to the study done by Naqvi et al [13] while higher incidence was observed by Chandanwale et al [12] The incidence of nonHodgkin's lymphoma in this study was 5.22%.…”
Section: Discussionsupporting
confidence: 90%
“…Teratocarcinoma encountered 12.1% incidence in this study, which is comparable to the studies done by Naqvi et al [13] and Karki and Bhatta. [19] Yolk sac tumor accounted for 5.22% of this study, which was comparable to the figures 5.8% and 6.8% given by Deore et al [18] and Naqvi et al [13] Most of the cases were seen in first decade. The incidence of other mixed germ cell tumors, that is, embryonal carcinoma and seminoma and Teratoma and seminoma was 4.3% and 3.4%, respectively which is comparable to the study done by Naqvi et al [13] while higher incidence was observed by Chandanwale et al [12] The incidence of nonHodgkin's lymphoma in this study was 5.22%.…”
Section: Discussionsupporting
confidence: 90%
“…The most represented age group is 20-29 years old (25%). These results are closer to those of Karki S and Bhatta RR [12] who, in a 5year study in Nepal of 70 cases, concluded that most malignant cases occurred between 40 and 50 years of age and that testicular tumors usually occur in 3 ages ie childhood, from post adolescence to young adults (20-35 years old) and among those over 50 years old. Following our study, we find that testicular swelling is the most common physical sign in the gait in malignant tumors-8 cases (100% of the specified cases).…”
Section: Discussionsupporting
confidence: 84%
“…In our study, non neoplastic lesions of testis were more common than neoplastic lesions (90.1% vs. 9.8%) which are correlating with other Indian studies as shown in Table 3. 5,[9][10][11] We found undescended testis (46.1%) as the most common non neoplastic lesion. However, none of the cases showed malignancy.…”
Section: Discussionmentioning
confidence: 99%